Controllable Physical Synergized Triboelectricity, Shape Memory, Self‐Healing, and Optical Sensing with Rollable Form Factor by Zn cluster. Issue 18 (22nd April 2022) - Ahn, Dahye; Sun, Jingzhe; Han, Seunghye; Lee, Jiwoo; Jeong, Songah; Cha, Seokjun; Noh, Seonmyeong; Choi, Hyeongsub; Ren, Bingqi; Yoon, Hyeonseok; Kim, Hyungwoo; Park, Jong‐Jin
Abstract: To build devices offering users comfortable experience, it is important to focus on form factor and multifunctionality. In this study, for the first time, multifunctional Zn clusters with shape memory, self‐healing, triboelectricity, and optical sensing synergized with rollable form factor are designed and fabricated by coordinating COO − and Zn 2+ . As pore forming agent, Zn clusters produce hierarchical porous structure depending on Zn amount. Zn clusters are applied as message transmitters and charge containers in optical sensing and corona charge injection, respectively. Moreover, Zn clusters in PVB‐COO‐Zn serve as positive tribomaterial due to Zn ion doping effect, increasing the output performance as the Zn amount reaches 20 wt%. In addition, injecting positive charge into PVB‐COO‐Zn 20 lead to more than 24 times increase in output performance compared to those of non‐porous structures. The reversibility of Zn clusters endows shape memory and self‐healing, synergized with the rollable form factor. The rollability is implemented using the long alkyl chain and the energy absorption of porous structure, providing damage resistance. The advancements in this work provide opportunities for multifunctional and unique applications (shape memory rotating‐triboelectric nanogenerator, rollable self‐healing touchpad, hidden tag) synergized with rollability that accomplishes working in broadened condition in near future. Abstract : Multifunctions with triboelectricity, shape memory, self‐healing, and optical transmitting property integrated with rollable form factor controlled by Zn clusters are designed and fabricated through coordinating carboxylate (COO − ) and Zn ion (Zn 2+ ). Enhanced rollability is endowed by introducing long alkyl chain and energy absorption of porous structure, which dissipates energy.